To the question about differentiation of remedies and liability in labour law - Черкасов, О. В. (Theory and practice of jurisprudence, 2016)
The nature and significance of protective measures in the branch of labor law were considered in the article. Features, distinguishing remedies and liability in labor law, and the basic criteria for such separation were identified. Peculiarities of the separate measures of coercion in labor law were also analyzed.